2017
DOI: 10.1002/ejoc.201601458
|View full text |Cite
|
Sign up to set email alerts
|

A Photocatalytic Meerwein Approach to the Synthesis of Isochromanones and Isochromenones

Abstract: A visible-light RuII photoredox Meerwein synthesis of isochromanones and isochromenones is described starting from diazonium salts of differently substituted anthranilic acids

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 64 publications
3
19
0
Order By: Relevance
“…Analogous results were obtained when the substitution pattern on both the diazonium salt and the alkene was varied, results that paralleled those reported by König and Fagnoni [5]. In our hands reactions were slower (6–8 h vs 2 h), probably due to the lower loading of photocatalyst (0.5% vs 2%) and excess of alkene (2 equiv vs 3 equiv) employed; moreover, the use of an inert atmosphere did not lead to significant improvements.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Analogous results were obtained when the substitution pattern on both the diazonium salt and the alkene was varied, results that paralleled those reported by König and Fagnoni [5]. In our hands reactions were slower (6–8 h vs 2 h), probably due to the lower loading of photocatalyst (0.5% vs 2%) and excess of alkene (2 equiv vs 3 equiv) employed; moreover, the use of an inert atmosphere did not lead to significant improvements.…”
Section: Resultssupporting
confidence: 85%
“…Also trans -stilbene reacted under the reaction conditions, but the 3,4-disubstituted isochromanone was isolated in only 19% yield. Noteworthy, compounds 4c , 4d and 4f , whose synthesis was previously reported starting from carboxylic acids [5], were obtained with comparable yields.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Having found that radical arylation reactions with arenediazonium salts can be conducted under such simple reaction conditions, we finally evaluated whether the addition of the typical photocatalyst [Ru(bpy) 3 ]Cl 2 (2 mol %) could further improve the reaction outcome. From eight comparative experiments conducted with 4‐chlorophenyldiazonium chloride (or tetrafluoroborate) 5 a,a′ and the arenes 1 – 4 , thiophene, N ‐Boc pyrrole, 1,4‐benzoquinone, and benzene, only the two reactions to the thiophene‐ and benzoquinone‐derived biaryls 10 a and 12 a gave yields increased by 8 and 11 %, respectively, when the photocatalyst was present.…”
Section: Methodsmentioning
confidence: 99%
“…The isochroman‐1‐one (isocoumarin) moiety is a widely known structural motif in a variety of natural products possessing significant biological and pharmacological activities and therefore have gained immense synthetic interest (Fig. ). Similarly, isochroman‐1,3‐diones and isochroman‐1,4‐diones are also known to have enhanced biological properties.…”
Section: Introductionmentioning
confidence: 99%